Productivity Assessment and Economic Analysis of Teak Plantations in Different Agro-climatic Zones of Karnataka - Reddy, Milkuri Chiranjeva; Madiwalar, Somashekhar L. (Indian Forester, 2014)
Productivity assessment of teak plantations was carried out in different agro-climatic zones of Karnataka, viz. northern dry zone (NDZ), northern transition zone (NTZ), and hilly zone (HZ) at three age gradations viz. 10, 15 and 20 years and economics were computed. Observations on growth parameters like total clear bole height, dbh, basal and clear bole volume etc., were recorded on trees in 10 x 10 m sample plots and average data per hectare was calculated. Economic techniques like benefit-cost ratio (BCR), internal rate of return (IRR), net present value (NPV) and net returns were employed for analyzing economic feasibility of plantations. 20 year teak plantations raised on the farmlands of NTZ had 3 3 3 significantly higher clear bole volume (738.98 m /ha) than that in NDZ (313.22 m /ha) and HZ (322.86 m /ha). Net returns were considerably higher 20-year plantations of NTZ (1,19,52,900 `/ha) then NDZ (49,92,622 `/ha) and HZ plantations (51,59,895 `/ha). Optimal average annual rainfall of 749 mm and medium black soil in NTZ have contributed to the higher biomass in teak. Poor rainfall in NDZ (<585 mm) and poor soil conditions (lateritic formations) in HZ must have contributed to the poorer growth of teak thus economic returns in these zones.